Removal of Malathion Insecticide from Water by Employing Acoustical Wave Technology - AM Fadaei; MH Dehghani; M Shayeghi (Tehran University of Medical Sciences, 2011)
Background: Organophosphorus pesticides are one of the most prevalent usages for pest control in the country. Such pesticides enter into water sources by different routes. Since drinking of contaminated water at the higher doses than the standard level, may causes undesirable effects to human health and ecosystem. The object of this research was to investigate the effect of various parameters including time, power and concentration on sonodecomposition of malathion insecticide in the water.Methods: The sonochemical degradation of malathion was investigated using acoustic wave technology (AWT). AWT with 130 kHz was used to study the decomposition of insecticide solution. Samples were analyzed using HPLC at different intervals times. Effectiveness of AWT at different times (20, 40, 60, 80, 100, and 120 minutes), concentrations of malathion at 2, 4 and 8 mg/L as well as powers of device (300W, 400W, 500W) are compared.Results: These findings showed that the degradation of the malathion insecticide at lower concentrations was greater in comparison to higher concentrations. Also, there was positive correlation between power increasing and the ability to malathion degradation. Conclusion: The sonodegradation of malathion at different concentrations and powers was successfully achieved. It has been shown that acoustical wave technology can be used to reduce the concentration of dissolved insecticide using high frequency.